DEVELOPMENT OF STUDENTS’ LEARNING ACTIVITY THROUGH TEACHING CHEMISTRY - Marat Akhmetov (Science & Research)

(untitled)
Today learning activity of students becomes a great significance for success of both education and life. There are at least two concepts of learning activity. One of these concepts considers learning activity as characteristic of personality. The second concept considers that learning activity is a learning action. Learning activity as characteristic of personality includes three levels. First level is reproducing activity. If students have some knowledge of chemistry they can achieve second level was named interpretative activity. Third level is creative activity. Researchers in chemical education consider mainly learning activity as action. Many methods of stimulating students’ learning activity have been developed, but problem of improving learning activity as characteristic of personality in chemical education has not been resolved. Theoretical and experimental research allowed us to create the pedagogical model for improving learning activity of students as characteristic of personality. Reproducing activity requires stimulating motives for learning. Motives “interestingly” and “usefully” are very helpful for this aim. Improving of interpretative activity requires a success in learning was achieved. The concept of cognitive strategies is very useful to improve a creative activity. There is difference between terms “cognitive strategy” and «learning method”. “Learning method” is a particular way of studying. “Cognitive strategy” is a mental technology of thinking. We tried to help all chemical teachers to realize the model. We had formulated 7 simple rules with the aim of improving learning activity of students.